The growth of distributed generation and associated challenges: A Great Britain case study. Issue 9 (9th February 2022) - Gordon, Samuel; McGarry, Connor; Bell, Keith
Abstract: Great Britain has reached high penetrations of distributed generation (DG). Historically, there has been a lack of technical requirements for DG to provide system support and for network operators to monitor, control and gather detailed information on DG installations. As a result, much of it is unobservable and uncontrollable. This work has analysed the available data sources for the amount, size and type of DG installations in GB. It is found that the lack of transparency and consistency of data are likely to act as an obstacle to the development of a more active distribution network. The impact that high DG has on system operation and system stability is discussed, including the potential for DG to offer flexibility services. A system disturbance in GB on August 9th 2019 brought a number of issues into focus: Slow action to change inappropriate settings of DG loss‐of‐mains protection and the uncertainty that DG adds to the effectiveness of under frequency load shedding schemes. Finally, it is argued that coordination between transmission and distribution networks is central to addressing many of the challenges and is a key enabler to utilising the flexibility available from DERs and releasing capacity for more DERs to be connected.